Application of Metal Oxide Nanoparticles in Different Carcinomas - Nutan Rani; Yousuf Khan; Sapna Yadav; Kalawati Saini; Dipak Maity (Journal of Nanotheranostics)
Metal oxide nanoparticles (MONPs) have recently attracted much attention from researchers due to their use in cancer chemotherapy, targeted drug delivery, and diagnosis/MRI imaging. Various studies have demonstrated that different metal oxide NPs show cytotoxic effects by inducing apoptosis in cancerous cells and do not have any toxic impact on normal cells. The mechanism of cytotoxicity is shown through reactive oxygen species (ROS) generated by (MONPs) in the cancerous cell. In vitro and in vivo studies reveal that in some cases metal oxide NPs are used alone and somewhere these NPs are used in combination with other therapies such as photodynamic therapy and with anticancer nanomedicines as drug carriers or drug conjugates. The phenomenon of enhanced permeability and retention (EPR) effect has been the basis of targeted drug delivery to cancerous tumors. Finally, we also provide a simple and comparative analysis of the major apoptosis pathways proposed to increase beginner understanding of anti-cancer nanomaterials. Herein, we have reviewed the most important antitumor results obtained with different metal oxide nanoparticles such as ZnO, Fe2O3/Fe3O4, CuO/Cu2O, TiO2, CeO2, and HfO2, respectively. These NPs can be applied to treat cancer by either passive or active processes. A passive process uses the enhanced permeability and retention (EPR) effect. Superparamagnetic iron oxide nanoparticles (SPIONs), due to their unique magnetic and physiochemical properties have been used in magnetic fluid hyperthermia (MFH) and magnetic resonance imaging (MRI) in vitro as well as in vivo. Now, the research has reached the stage of clinical trials for the treatment of various types of cancer. ZnO NPs have been used very vastly in cytotoxic as well as in targeted drug delivery. These NPs are also used for loading anticancer drugs such as doxorubicin. Herein, in this review, we have examined current advances in utilizing MONPs and their analogs as cancer therapeutic, diagnostic, and drug-delivery agents.